(untitled) (Cadernos de Sociomuseologia, 2024)
This paper investigates the power institutions have in relation to providing information in the structure of labels regarding their collection, whether displayed in the form of a permanent framework, or within more defined temporalities, as in the case of changing exhibitions. It tackles, in particular, the presentation of information from the perspective of postcolonial questions. The possibility of discussing significant and emerging concerns related to heritage possession and presentation constitutes a vital arena to examine, in particular, the presence of artists engaged critically with the museum identity and devices. This analysis will demonstrate that the potential for addressing significant issues resides within the artists’ sphere of action. Fred Wilson’s groundbreaking exhibition "Mining the Museum" (1992) serves as another extraordinary reference point, highlighting how artists can profoundly impact and reshape narratives within institutional settings. The current disputes regarding the presentation of works of art are presented with a brief reference to the project "Revision of works’ titles" at the Staatliche Kunstsammlung Dresden, in Germany. Keywords: Museology; Collection; Postcolonialism; Conceptual Art